2018
DOI: 10.1589/jpts.30.874
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blind study to assess if vitamin D treatment affects the outcomes of rehabilitation and balance in hemiplegic patients

Abstract: [Purpose] To investigate the effect of vitamin D supplementation on rehabilitation outcomes and balance in patients having hemiplegia due to ischemic stroke. [Subjects and Methods] Vitamin D levels of 132 patients hospitalized for hemiplegia rehabilitation due to ischemic stroke were tested. Consequently, 86/132 patients had low vitamin D levels, 72 of which met the inclusion criteria and were included in the study. Patients were divided into two groups: Group A (injected with 300,000 IU vitamin D), and Group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 22 publications
3
33
1
Order By: Relevance
“…28,29 One study reported that vitamin D supplementation exerted a positive effect on the balance score of stroke patients. 30 Because impaired sensations are associated with balance disorder in stroke patients, our results are coherent with the available literature. Electrophysiological data suggest that the time needed to document the changes in Berg balance test scores is >8 weeks, which corresponds to axonal regeneration time.…”
Section: Discussionsupporting
confidence: 90%
“…28,29 One study reported that vitamin D supplementation exerted a positive effect on the balance score of stroke patients. 30 Because impaired sensations are associated with balance disorder in stroke patients, our results are coherent with the available literature. Electrophysiological data suggest that the time needed to document the changes in Berg balance test scores is >8 weeks, which corresponds to axonal regeneration time.…”
Section: Discussionsupporting
confidence: 90%
“…Vitamin D was the most commonly used self-care product in our study and while there is evidence that Vitamin D 40 and omega 3 41 levels may have an inverse relationship with stroke risk, the evidence that they each improve rehabilitation outcomes remains promising but preliminary. [42][43][44] Interestingly, while the self-care products used by stroke survivors in our study have limited clinical evidence for such use, clinical research does support the use of tai chi by chronic stroke patients to improve balance, gait and quality of life 45 but not stroke prevention. 46 Small-scale studies suggest yoga may improve anxiety and depression in chronic stroke patients, but the improvements on balance and overall quality of life have been consistently nonsignificant.…”
Section: Discussionmentioning
confidence: 65%
“…St John's Wort ( Hypericum perforatum ), a self‐care product reported to be used by stroke survivors in our study, has high level evidence of effectiveness in the treatment of mild to moderate depression 39 but has not yet been studied or assessed in stroke patients. Vitamin D was the most commonly used self‐care product in our study and while there is evidence that Vitamin D 40 and omega 3 41 levels may have an inverse relationship with stroke risk, the evidence that they each improve rehabilitation outcomes remains promising but preliminary 42‐44 . Interestingly, while the self‐care products used by stroke survivors in our study have limited clinical evidence for such use, clinical research does support the use of tai chi by chronic stroke patients to improve balance, gait and quality of life 45 but not stroke prevention 46 .…”
Section: Discussionmentioning
confidence: 67%
“…For example, two small unblinded studies among individuals with vitamin D insufficiency or deficiency who experienced an ischemic stroke suggested that vitamin D supplementation after stroke may result in larger improvements in the Scandinavian Stroke Scale [25] or lower modified Rankin Scale scores [26] than individuals assigned to no supplementation. A blinded trial among 132 individuals with hemiplegia due to ischemic stroke observed that an intramuscular injection of 300 000 IU vitamin D resulted in increased activity levels and accelerated balance recovery but did not affect ambulation or motor recovery compared with a saline injection [27]. In contrast, a blinded trial among 100 hospitalized patients undergoing rehabilitation after acute stroke observed no significance differences in the gain in Barthel Index score between those randomized to receive 2000 IU/day of vitamin D3 and those randomized to placebo [28].…”
Section: Discussionmentioning
confidence: 99%